Biochemical Profile of Milk of Buffalo (Bubalus bubalis), Cow (Bos taurus) and Goat (Capra hircus): Potential Candidates for Supporting the Growth of Leishmania donovani Promastigotes in Culture Medium as Alternative to Fetal Bovine Serum (FBS) - Muniaraj, M.; Kumar, S.; Lal, C. S.; Sinha, P. K. (Journal of Buffalo Science, 2012)
The milk of cow (Bos taurus), buffalo (Bubalus bubalis), and goat (Capra hircus) were investigated for thebiochemical profile such as glucose, total protein, triglycerides, cholesterol and calcium. Although used as potentialcandidate to replace fetal bovine serum in the culture medium for the cultivation of parasitic protozoan such asLeishmania donovani promastigotes, the biochemical profile of milk will provide information about which factor supportsand essential for the growth of parasite. We found triglycerides were predominant in goat followed by cow and buffalomilk. The level of cholesterol was high in buffalo milk followed by goat and FBS. The level of calcium was high in buffalomilk followed by goat and cow milk.